P43 for manufacturing of large area scintillating screens. (1st August 2022) - Balakin, V.; Meshkov, O.; Ulianitsky, V.; Rogovsky, Yu.; Semenov, A.; Ageeva, N.; Ivanova, S.; Skaballanovich, T.; Smirnov, A.; Medvedeva, K.
Abstract: This paper describes investigation of scintillator P43 coating for large area screens intended for preliminary beam diagnostics in the Collector Ring (Facility for Antiproton and Ion Research in Europe). We used two appropriate coating techniques: detonation spraying and electrophoresis. The article contains short descriptions of the Collector Ring, screen coating techniques, light output (with application of electron welding), and vacuum tests. We also applied SEM to check the structure and chemical composition of pure P43 powder and scintillation screen samples, prepared by detonation spraying and electrophoresis coating techniques. As a result, we observed poor P43 light output after detonation spraying (the reason is a change in the chemical composition of P43) and poor ruby and alumina light output in comparison with P43 in the case of the electrophoresis technique. Improving of the electrophoresis technique enabled us to reach good adhesion and vacuum properties without decrease in the light yield.